A metabolite panel that differentiates Alzheimer's disease from other dementia types. Issue 7 (17th November 2021) - Jia, Longfei; Yang, Jianwei; Zhu, Min; Pang, Yana; Wang, Qi; Wei, Qin; Li, Ying; Li, TingTing; Li, Fangyu; Wang, Qigeng; Li, Yan; Wei, Yiping
Abstract: Introduction: Alzheimer's disease (AD) is associated with altered metabolites. This study aimed to determine the validity of using circulating metabolites to differentiate AD from other dementias. Methods: Blood metabolites were measured in three data sets. Data set 1 (controls, 27; AD, 28) was used for analyzing differential metabolites. Data set 2 (controls, 93; AD, 92) was used to establish a diagnostic AD model with use of a metabolite panel. The model was applied to Data set 3 (controls, 76; AD, 76; other dementias, 205) to verify its capacity for differentiating AD from other dementias. Results: Data set 1 revealed 7 upregulated and 77 downregulated metabolites. In Data set 2, a panel of 11 metabolites was included in a model that could distinguish AD from controls. In Data set 3, this panel was used to successfully differentiate AD from other dementias. Discussion: This study revealed an AD‐specific panel of 11 metabolites that may be used for AD diagnosis.